2015
DOI: 10.2217/epi.14.80
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Alterations of DNA Methylation Machinery in Human Diseases

Abstract: DNA methylation plays a critical role in the regulation of chromatin structure and gene expression and is involved in a variety of biological processes. The levels and patterns of DNA methylation are regulated by both DNA methyltransferases (DNMT1, DNMT3A and DNMT3B) and 'demethylating' proteins, including the ten-eleven translocation (TET) family of dioxygenases (TET1, TET2 and TET3). The effects of DNA methylation on chromatin and gene expression are largely mediated by methylated DNA 'reader' proteins, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
150
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(157 citation statements)
references
References 116 publications
6
150
0
1
Order By: Relevance
“…9) DNMTs can catalyze Pcarelated gene nuclear factor-E2-related factor 2 (Nrf2) 10) and RASSF1A 11) methylation that promotes tumor progression. Gravina et al analyzed the correlation between ectopic expression of DNMT1, DNMT3a and DNMT3b and tumorigenic capacity of prostate cancer cells and concluded that the increased methylation in more aggressive tumors supporting the use of DNMTs in advanced prostate cancer.…”
mentioning
confidence: 99%
“…9) DNMTs can catalyze Pcarelated gene nuclear factor-E2-related factor 2 (Nrf2) 10) and RASSF1A 11) methylation that promotes tumor progression. Gravina et al analyzed the correlation between ectopic expression of DNMT1, DNMT3a and DNMT3b and tumorigenic capacity of prostate cancer cells and concluded that the increased methylation in more aggressive tumors supporting the use of DNMTs in advanced prostate cancer.…”
mentioning
confidence: 99%
“…A family of DNA methyltransferases transfer a methyl group from S-adenosyl methionine to the fifth carbon of a cytosine residue to form 5-methylcytosine, thereby catalyzing DNA methylation. This modification can be inherited through cell division (24). Beside its involvement in normal development in human beings, DNA methylation is frequently implicated in the onset or course of cancer due to its roles in many other regulatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…5hmC is recognized poorly by Dnmt1 and can lead to replication-dependent passive demethylation. 5hmC can be further oxidized by Tet proteins to produce 5fC and 5caC [28] . Alternatively, 5hmC…”
Section: Dna Methylation Methods For the Specific Genelocus Specificmentioning
confidence: 99%